Environmental conflict and cooperation premise, purpose, persuasion, and promise - Lee, James R. 1951- (Routledge, Taylor & Francis Group, 2020)
"Environmental Conflict and Cooperation explores the evolution of environmental conflict as a field of research and the study of cooperation as an alternative to war. Over four key Parts, James Lee navigates the contours of this growing field and paints a vivid framework for better understanding issues around environmental conflict and security: - 1. The premise of the field and its historic manifestations - 2. The definition and purpose of research - 3. The persuasions or types of environmental conflict and cooperation - 4. The promise of research in leading to better decision-making and to broaching new challenges. Over the course of these Parts, the author outlines the deep historic record of this discipline, arguing that it will play a key role in understanding important future trends. Utilizing a wide variety of case studies that range from ancient examples including conflict over the Cedars of Lebanon and the role of tin in the Peloponnesian Wars, to future-oriented scenarios including expanded island-building in the South China Sea and the global politics of geo-engineering, Lee highlights key concepts, metrics, and policy contexts that will test current understandings. He also examines a variety of research methods and provides examples of the ways in which such research can be used to inform policy improvements. This book will draw specific interest from students and scholars of environmental conflict and cooperation, as well as researchers of environmental politics and security studies"--
Keywords: Umweltkrieg; Politischer Konflikt; Konfliktlösung; Friedenssicherung; International relations / Environmental aspects; Peace-building / Environmental aspects; Conflict management / Environmental aspects; War / Environmental aspects; Natural resources / Management / International cooperation